Determinants of outward foreign direct investment in developing countries: a case of Malaysia / Rosfadzimi Mat Saad and Abd Halim Mohd Noor - Mat Saad, Rosfadzimi; Mohd Noor, Abd Halim (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
With the advance of globalization, foreign direct investments are no longer limited to the developed nations. Increasingly FDIs between developing countries are rivalling traditional FDIs. Outward Foreign Direct Investment, OFDI is one of the measures to indicate the performance and capability of developing countries enterprises in economic integration where border barriers are eliminated. Malaysia as a developing economy is undertaking OFDI due to the limitation of local resources and to search for new markets. This paper studies the determinants of OFDI by Malaysia based firms. It focused on trade-related, domestic push factors and home countries’ capability drivers in determining the factors influencing OFDI. The period under study is from 1980 to 2008. Simple multiple regression analysis is used in the study. Several variables are used to proxy OFDI, but export and productivity level are found significant in influencing OFDI.